Vertebral bone microarchitecture and osteocyte characteristics of three toothed whale species with varying diving behaviour - Tim Rolvien (Nature Portfolio, 2017)
Abstract Although vertebral bone microarchitecture has been studied in various tetrapods, limited quantitative data are available on the structural and compositional changes of vertebrae in marine mammals. Whales exhibit exceptional swimming and diving behaviour, and they may not be immune to diving-associated bone pathologies. Lumbar vertebral bodies were analysed in three toothed whale species: the sperm whale (Physeter macrocephalus), orca (Orcinus orca) and harbour porpoise (Phocoena phocoena). The bone volume fraction (BV/TV) did not scale with body size, although the trabeculae were thicker, fewer in number and further apart in larger whale species than in the other two species. These parameters had a negative allometric scaling relationship with body length. In sperm whales and orcas, the analyses revealed a central ossification zone (“bone-within-bone”) with an increased BV/TV and trabecular thickness. Furthermore, a large number of empty osteocyte lacunae was observed in the sperm whales. Quantitative backscattered electron imaging showed that the lacunae were significantly smaller and less densely packed. Our results indicate that whales have a unique vertebral bone morphology with an inside-out appearance and that deep diving may result in a small number of viable osteocytes because of diving depth-related osteocyte death.